Permafrost distribution in the southern part of the discontinuous zone in Québec and Labrador - Brown, Roger (Géographie physique et Quaternaire, 1979)
The distribution of permafrost in the southern part of the discontinuous zone in Québec and Labrador is described. At the southern limit of this subzone islands of permafrost vary in extent from a few tens of square metres to several hectares and in thickness from a few centimetres to a metre or so. Northward to the middle of the discontinuous zone permafrost becomes increasingly widespread reaching a thickness exceeding 100 metres. Permafrost occurs mainly in peatlands, on some north facing slopes and above treeline on mountain summits. The relationships of permafrost distribution to climatic and terrain factors, including air temperature, vegetation, drainage and snow cover are discussed, the last being particularly important. The paper concludes with an analysis of some prominent air photo patterns.